Assessment of the customer data usage and perceived service quality in managing customer relations in banking industry: A case of CRDB - Tairo, Ester C (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the award of the Degree of Master of Science in Marketing Management (MSc-MKT) of Mzumbe University Dar es Salaam Campus College.